Chromosome stability in cryopreserved germplasm of Cyrtopodium hatschbachii (Orchidaceae) - Surenciski, Mauro Rodrigo (2007)
Cyrtopodium hatschbachii is a recently-described orchid species distributed in norteastern Argentina. Natural populations of this species require conservation because they have a very restricted size and distribution and are in danger of destruction. Cryopreservation in liquid nitrogen is the most commonly-applied technique for ex situ conservation of plant genetic resources, but genetic stability after cryopreservation is an important consideration. Chromosome number and morphology are primary cytogenetic parameters that must remain stable after cold storage. We analyzed plants of C. hatschbachii cytogenetically in order to determinate their stability level. The plants from cryopreserved encapsulated seeds were stable at chromosome and phenotypic level, but showed more limited condensation of the chromatin during the first stages of their development. The chromosome number and karyotype analysis of C. hatschbachii is presented for the first time.